Cardiac Computed Tomography-Derived Left Atrial Strain and Volume in Pediatric Patients With Congenital Heart Disease: A Comparative Analysis With Transthoracic Echocardiography - Xie, Wei-Hui; Chen, Li-Jun; Hu, Li-Wei; Ouyang, Rong-Zhen; Guo, Chen; Sun, Ai-Min; Wang, Qian; Qiu, Hai-Sheng; Zhang, Yu-Qi; Zhang, Hao; Fu, Qi-Hua; Zhong, Yu-Min (Frontiers in Cardiovascular Medicine, 2022)
Purpose: This study aimed at exploring the feasibility and reproducibility of CCT for the measurement of LA strain and volume compared with transthoracic echocardiography (TTE) in pediatric patients with congenital heart disease (CHD). Materials and methods: The present study included 43 postoperative patients with CHD (7.39±3.64 years, 56% male) who underwent clinically indicated CCT and all patients underwent additional TTE on the same day. LA strain and volume parameters were measured by dedicated software. The correlation and agreement of LA strain and volume parameters were assessed using Pearson’s correlation coefficient and Bland-Altman analysis. Intra-class correlation coefficients (ICC) were used to assess CCT intra-observer and inter-observer reproducibility. Results: All strain parameters of CCT were lower compared to TTE (reservoir strain: 28.37 ±6.92 vs. 32.15±8.15, respectively; conduit strain: 21.33±6.46 vs. 24.23±7.75, respectively; booster strain: 7.04±2.74 vs. 7.92±3.56). While the volume parameters of CCT were higher compared to TTE (LAV: 29.60±19.01 vs. 25.66±17.60, respectively; LAVi:30.36±22.31vs.28.63±19.25, respectively). Both LA strain and volume measurements showed good correlation and agreement between the two modalities (r = 0.63-0.87, p< 0.001). CT-derived LA strain and volume measurements showed good intra- and inter-observer reproducibility using prototype software (ICC = 0. 78–0.96). Conclusions: CCT was feasible for measuring LA strain and volume with good correlation and high reproducibility as compared with TTE. As a complementary modality, CCT can regard as an accepted method in the evaluation of LA function in pediatric patients with CHD